Cultivating Well-being, Community Cohesion, and Sense of Purpose through African Contemplative Practices - Lucy Draper-Clarke; Caryn Green (Creative Arts in Education and Therapy)
Exploring Southern African contemplative traditions addresses an important gap in the fields of contemplative science and healing modalities. In contrast to meditation practices drawn from Eastern wisdom traditions, practices embedded in African spirituality are sound- and movement-based and conducted in community settings. During a research retreat in South Africa, attended by traditional healers, creative arts therapists and performers, mindfulness and neuroscience researchers, and a Buddhist monk, indigenous rituals were performed by experienced facilitators and analyzed through group reflection sessions. Phenomenological data were recorded and coded. Participants identified how the synchronized movements, vocalization, and multisensory listening enabled experiences of self-transcendence, connection, and social cohesion, eliciting emotions of peacefulness, harmony, and joy. Using thematic analysis, four recurring threads emerged: sacred sense of purpose, nervous system self-regulation and co-regulation, enhancement of pro-social qualities, and community cohesion. These findings are presented to support international dialog and illuminate relationships among Eastern, Western, and African wisdom traditions. The global decline in mental health provides increased relevance, exacerbated by the COVID-19 pandemic and the impact of perpetuated historical injustices that have rendered individuals and communities isolated and disconnected. This article proposes that embodied rituals and arts-based therapies, alongside mindfulness practices, could provide effective ways to enhance personal well-being and build community cohesion.